Sisi Gelap Media Sosial: Ranah Sosial-Politik - mustofa mustofa mustofa (iLearning Journal Center, 2019)
This study wants to elaborate on phenomenon of the use of social media in the socio-political realm which lately often seems less polite, such as the spread of hoaxes and hate speech which often lead to acts of persecution or violence. Using a qualitative approach and library research method, this study aims to explore online documents and data related to the existence of social media and its negative effects. In this study, social media is concerned with all networks to communicate using the internet and chosen purposively and not limited to the location of their use. The results of this study showed that the practice of 'abuse' of social media is often found in the socio-political realm, whose peak can be seen during the implementation of the 2017 DKI Jakarta Governor Election. Social media, which should be a medium of political education or space to exchange ideas on various political issues, precisely used by its users to impose the interests of their own groups.